2012
DOI: 10.3324/haematol.2012.068478
|View full text |Cite
|
Sign up to set email alerts
|

Molecular pathogenesis of Waldenstrom's macroglobulinemia

Abstract: Waldenström's macroglobulinemia is an indolent, lymphoproliferative disease, characterized by a heterogeneous lymphoplasmacytic bone marrow infiltrate and high immunoglobulin M production. While technological advances over the past several decades have dramatically improved the possibilities of studying the molecular basis of Waldenström's macroglobulinemia, the pathogenesis of the disease remains fragmented. Undoubtedly, research has been successful in uncovering underlying aberrations and deregulated mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 89 publications
1
28
0
2
Order By: Relevance
“…Future high-resolution technique studies may confirm the MAR we have identified as a potential target area for use of a new FISH probe for identification of WM with partial trisomy 4. Interestingly, trisomy 4 seems to be unique in WM across low grade B-cell neoplasia [6,31,32], and was also more frequently observed in symptomatic cases. No candidate gene was discovered to date on chromosome 4 in WM, although numerous important genes are located on chromosome 4 and study of the wholegenome sequencing suggested alterations on chromosome 4 [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future high-resolution technique studies may confirm the MAR we have identified as a potential target area for use of a new FISH probe for identification of WM with partial trisomy 4. Interestingly, trisomy 4 seems to be unique in WM across low grade B-cell neoplasia [6,31,32], and was also more frequently observed in symptomatic cases. No candidate gene was discovered to date on chromosome 4 in WM, although numerous important genes are located on chromosome 4 and study of the wholegenome sequencing suggested alterations on chromosome 4 [7].…”
Section: Discussionmentioning
confidence: 99%
“…Waldenstrom's macroglobulinemia (WM) is a rare lymphoproliferative disorder characterized by bone marrow (BM) infiltration of lymphoplasmacytic cells associated with serum IgM paraprotein [5,6]. The most recent discovery was the high frequency of MYD88 L265P mutation identified in WM [7].…”
Section: Introductionmentioning
confidence: 99%
“…High-throughput genomic studies have identified multiple mechanisms of genetic changes in Waldenstr€ om macroglobulinemia including several recurrent CNA such as deletion 6q, deletion 13q, or gain of chromosome 4 and CN-LOH (15,27). This genomic pattern segregates further Waldenstr€ om macroglobulinemia among the others B-cell tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrent deletions on 13q14 and 17p13 have been mostly seen in more advanced stages of the disease [4]. Although not unique to WM, inactivating mutations of TRAF3 (located on cytoband 14q32.32) lead to constitutive activation of NF-κB pathways and are recurrent findings in a small percentage (~5%) of WM patients [10].…”
Section: Workupmentioning
confidence: 99%
“…The bone marrow pattern is predominantly intertrabecular [9]. The immuno-phenotype of WM consists of expression of pan-B-cell markers (CD19, CD20, CD22), cytoplasmic immunoglobulin (cIg), FMC7, CD38, and CD79a [10]and typically negative for CD3 and CD103 [9]. The plasma cells number is generally in the normal range, but they differ from normal and myeloma cells by being positive for CD38, and commonly express CD19, CD45, and CD20, but lack CD56 [10].…”
Section: Diagnosismentioning
confidence: 99%